Early Intervention Program by Utilizing Family Resources to Achieve Autonomy for Children with Autism - Anni Sinaga; Achmad Hufad; Endang Rochyadi (Department of Special Education, 2021)
Early intervention implementation must be carried out in its natural environment through family empowerment because it is more effective than an early intervention that focuses on children. This condition is based on home and family as a natural environment for children. The intensity of interaction and communication between children and families greatly influences achieving optimal child development. This study aims to optimize children who are known to have risks and children who have definitive obstacles in children aged 0 to 6. The implementation is focused on support, increasing the skills, and other positive aspects that exist in the family. The approach uses a qualitative method with a case study approach. Data collection was carried out through interviews, observation, and document study. The results show an effect of early intervention on the development of children who have communication barriers based on the subject assessment with parents. The conclusion of the implementation of the early intervention program is a change in the family paradigm towards the needs of their children, and the family also begins to understand that their children need a lot of vocabulary to increase their self-confidence.